Telfairia occidentalis ATTENUATES LIVER DAMAGE IN STREPTOZOTOCIN-INDUCED DIABETIC WISTAR RATS - U. P., Ujong,; E., Nkanu, E. (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2021)
Background: The onset of diabetes is associated with the development of biochemical and functional abnormalities, including oxidative stress and apoptosis in the liver. Telfairia occidentalis (TO) is a popular plant and food item reported to have high of antioxidant, anti-inflammatory, immunomodulatory and hypoglycemic properties. The present study investigated the potential antihepatotoxic properties of T. occidentalis in animal model of diabetes- induced liver damage. Methods: Thirty-five rats were assigned into five groups of Seven (7) animals each. Group 1 (Normal control) received 0.5ml distilled water for 28 days, Group 2 (Diabetic control) received 10% fructose (w/v) for 14 days prior to single intra-peritoneal injection of 40mg/kg body weight streptozotocin (STZ), Group 3 (TO1 group), received 10% fructose (w/v) for 14 days prior to single intra-peritoneal injection of 40mg/kg body weight STZ, followed by treatment with 200mg/kg body weight TO for 28 days, Group 4 (TO2 group) received 10% fructose (w/v) for 14 days prior to single intra-peritoneal injection of 40mg/kg body weight STZ, followed by treatment with 300mg/kg body weight TO for 28 days, while Group 5 (MET group) received 10% fructose (w/v) for 14 days prior to single intra-peritoneal injection of 40mg/kg body weight STZ, followed by treatment with 300mg/kg body weight Metformin for 28 days. Results: Treatment with TO at 200mg/kg and 300mg/kg significantly (p<0.05) augmented the activities of superoxide dismutase, catalase an glutathione peroxidase as well as reduced glutathione level with a concomitant decrease in malondialdehyde level in the liver of diabetic rats. Also, Inflammatory biomarkers namely TNF-α, IL-1β, NO and iNOS levels along with MPO and COX-2 activities were significantly decreased in the liver of diabetic rats when treated with T. occidentalis (200mg/kg and 300mg/kg). Furthermore, the activity of caspase-3 was markedly reduced in the liver of diabetic rats when treated with T. occidentalis (200mg/kg and 300mg/kg). Conclusion: Telfairia occidentalis attenuated oxidative stress, inflammation and activation of caspase-3 in the liver of streptozotocin-induced diabetic rats via antioxidant and anti-inflammatory mechanisms.